ELT and Social Justice in Multilingual Classrooms - Kapur, Kirti (Babylonia Journal of Language Education, 2021)
The challenge for educators and policy-makers is to ensure that the rights of all school children are respected, and the cultural, linguistic and economic resources of the nation are maximized. Today this is all the more relevant because many languages are becoming endangered and some have actually disappeared from the Indian linguistic landscape despite our claims to multilingualism and maintenance. The loss of a language is equivalent to the loss of an entire culture in itself. The first task of the school becomes relating home language to second language. In this manner more languages can be integrated and there is a movement towards other languages without losing the first and English is not contextualized in a western ambience but is taught through a contextually rich local perspective.